Safety of ECT in patients receiving an oral anticoagulant - Nicolette R. Centanni, PharmD, BCPS, BCGP, BCPP; Wendy Y. Craig, PhD; Dena L. Whitesell, MD; Wesley R. Zemrak, PharmD, BCPS; Stephanie D. Nichols, PharmD, BCPS, BCPP, FCCP (Mental Health Clinician, 2021)
Introduction: This study assessed the use, tolerability, and safety of anticoagulation via direct oral anticoagulants or warfarin in medical and psychiatric inpatients receiving ECT. Methods: This retrospective cohort study included 32 patients who received ECT while on either a direct oral anticoagulant (9) or warfarin (23) and spanned 247 encounters at Maine Medical Center between December 2012 and December 2018. Data are presented descriptively and analyzed using SPSS version 25 and Microsoft Excel version 2016. Results: Among the 247 ECT patient encounters, there were few major adverse effects of ECT in this medically complex population. These adverse effects included headache during 4 encounters (1.6%), respiratory distress during 2 encounters (0.8%) and a cardiovascular event during 1 encounter (0.4%). One patient (3.1%) who was receiving concurrent rivaroxaban and venlafaxine experienced gastrointestinal bleeding that was determined to be unrelated to ECT. One patient on fluoxetine and warfarin experienced hemoptysis thought to be secondary to epistaxis. No other major bleeding or clotting event occurred during an ECT session nor for the duration of the hospitalization. Discussion: Direct oral anticoagulants and warfarin appear safe in the treatment of patients with atrial fibrillation or acute venous thromboembolism who are receiving concomitant ECT. Prospective studies are needed to confirm these findings.